ANALISIS SEMIOTIKA PIERCE: PERBANDINGAN POSTER IKLAN SAMPO DI TIONGKOK DAN INDONESIA - Kunmei, Li; Indira, Dian; Soeria Soemantri, Ypsi; Lupi Ardiati, Riza (Universitas Ahmad Dahlan, 2022)
Advertisements are packaged in such a way that it is very influential to convey messages and at the same time influence or suggest products to the public. In shampoo advertisements from one country to another, there are cultural peculiarities of the people. This research has a problem formulation, namely the character of shampoo advertising culture in China and Indonesia. In solving the problem formulation, this research uses Pierce's semiotic theory using data in the form of advertisements for the Pantene, Clear, and Sunsilk shampoo brands. The analysis is carried out with a qualitative method. The results of this study show that shampoo advertisements in China and Indonesia in general have similarities with displaying a picture of a woman, but both have their own character that shows a picture of the people of their respective countries.